Concepções de interdisciplinaridade de profissionais de saúde de um serviço de reabilitação e fisioterapia - Garcia, Christianne Fernandes [UNIFESP] (2016)
This study investigates the interdisciplinary concepts of health professionals working at the Shore/Intermediate Zone Recovery and Physical Therapy Section in Santos (Serfis-Zoi), also, relational aspects and team subjectivity development. One of the main drivers is the path followed by these professionals, their stories and perspectives with the intention to make possible an understanding of what reality is presented today at that Section, and identify how these professionals work or recognize the importance of an interdisciplinary study. Data collection was carried out for the research through focus groups considering the qualitative methodology, based on a socio-historical perspective as this is relevant to the field of subjectivity and symbolism. The participant group was professionals from Serfis, per four meetings held from the months of August and September of 2015 and, from the analysis of data, thematic areas were identified, which allowed to put together the dialogues into three categories: Building subjectivity, work processes and interdisciplinarity, which developed in ten subcategories. The results showed that the team identifies the importance of interdisciplinary work, but it does not depend only on the individual training or own career path. Also demonstrates that interdisciplinary teamwork presents difficulties and it?s still a challenge because results showed that other factors such as infrastructure, the service organization and even relational issues are part of it and make it difficult for the interdisciplinarity effectively happen. One of the main aspects relates to the very understanding of what would be an interdisciplinary work, which eventually merges with the multidisciplinary and also group communication and between staff and the different managements. The issues that emerged from the research indicate the need for changes in the organization and work system at Serfis, the implementation of strategies that contribute to better coordination between the different professionals that work there, among them, the implementation of dialogue and continuing education, built collectively, with the participation of the staff and management are the ones that stands out in the process of transformation. This study was intended to contribute effectively to the creation of interactions and dialogue in the unit in order to share own stories and exercise listening within the team, this service can establish strategies for interdisciplinary to work effectively.